Assessment of antibiotic appropriateness at discharge: experience from a quaternary care hospital setting. Issue 4 (11th July 2022) - Saleh, Joanna; El Nekidy, Wasim S; El Lababidi, Rania
Abstract: Background: There is a gap in antimicrobial stewardship in transitions of care. Objectives: To assess the appropriateness of antibiotics utilized and prescribing habits at hospital discharge. Methods: A retrospective, observational study was conducted at our quaternary care hospital between January 2021 and March 2021. During the study period, all patients discharged on antibiotics for pneumonia (PNA), skin and soft tissue infections (SSTI), urinary tract infections (UTI) and intra-abdominal infections (IAI) were included. The overall appropriateness of therapy was assessed based on the following combined criteria: agent, dose, frequency, duration of therapy, and ability to meet diagnostic criteria. Results: One hundred and forty-five subjects met the inclusion criteria. Of these, 44 (30.3%) were determined to have received overall appropriate antibiotic therapy. The most common infections were UTI, followed by IAI, PNA, and SSTI, respectively. Further, from the group deemed to have received overall inappropriate therapy, 26 of the 101 (25.7%) patients received an inappropriate antibiotic choice, 6 (5.9%) an inappropriate dose, and 84 (83.2%) an inappropriate duration of therapy. Conclusions: Inappropriate duration of therapy represented the most challenging problem with antibiotic regimens at discharge. Larger studies are needed to identify potential interventions that are effective, and can be implemented in all settings, including resource-limited ones.